(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
In healthcare "End of life" can be referred to the final stage of a person’s life, typically the last months or days, when they are facing death from a terminal illness, or it can refer to the final stage of a product’s usefulness before it is discarded or recycled. Frоm а prаcticаl pоint оf view, End-of-life issues relate to someone’s death and the time just before it, when it is known that they are likely to die soon from an illness or condition.